PECULIARITIES AND POSSIBLE REASONS OF FELDSPAR PORPHYROBLASTS ORIENTATION IN GRANITOIDS OF LYPNIAZHKA STRUCTURE - SHEVCHUK, V.; KOCHETOV, R.; YARESHCHENKO, S.; MARCHENKOV, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Dynamic-cinematic conditions of Lypniazhka granite-gneissic structure formation are investigated on the basis of the ratio of deformational and crystallization shistosity. It is expressed by megacrystals of the common potash feldspar. The change of a transtention conditions at the growth of porphyroblasts by conditions of transpression at late stages of a nucleus structure formation is demonstrated.